Modeling of an irrigation system in a virtual physical space - Todorka Glushkova (AIMS Press, 2021)
One of the major challenges that smart agriculture is expected to address is the efficient use of water resources. The conservation and the efficient use of clean water is a long-term strategy worldwide. Modeling of smart agriculture systems is an important factor because the processes there are very slow and sometimes it takes a year or more for a full crop cycle. At the same time, a large amount of data is usually needed to make informed decisions. This determines the importance of developing appropriate systems through which to simulate, generate, optimize and analyze various possible scenarios and prepare appropriate plans. In this paper, an infrastructure known as Virtual-Physical Space adapted for agriculture is presented. The space supports integration of the virtual and physical worlds where analysis and decision making are done in the virtual environment and the state of the physical objects (things) of interest is also taken into account at the same time. Special attention is paid to the possibilities for modeling an irrigation system. An ambient-oriented approach has been adopted, using the Calculus of Context-aware Ambients formalism as the basic tool for modeling agriculture processes. Furthermore, the supporting platform is briefly presented. Active components of the platform are implemented as intelligent agents known as assistants. Users (agriculture operators) are serviced by personal assistants. Currently, the presented modeling system is deployed over a two layered system infrastructure in the region of Plovdiv city. Plovdiv is the center of vegetable production in Bulgaria. The process of modeling intelligent irrigation systems and the current results are discussed in this paper.